Immobilized peptide asparaginyl ligases enhance stability and facilitate macrocyclization and site-specific ligation - Hemu, Xinya (2021)
The recently discovered peptide asparaginyl ligases (PALs) from cyclotide-producing plants are efficient and versatile tools for protein and peptide engineering. Here, we report immobilization of two glycosylated PALs, butelase-1 and VyPAL2, using three different attachment methods and their applications for peptide engineering. We compared immobilization indirectly via noncovalent affinity capture using NeutrAvidin or concanavalin A agarose beads or directly via covalent coupling of free amines on the enzyme surface with the N-hydroxysuccinimide (NHS) ester attached on agarose beads. The catalytic efficiency of immobilized PALs correlated with the distance between the biocatalysts and the solid supports, and in turn, the mobility of enzymes and the accessibility of substrates. Compared to their soluble counterparts, the site separations of immobilized PALs retain higher activity after prolonged storage and confer reusability for over 100 runs with less than 10% activity loss. We also showed that the cyclization and ligation of peptides and proteins with varying shapes and sizes can be accelerated by providing higher concentration of reusable immobilized PALs. These advantages could be exploited for large-scale industrial applications and nanodevices.